Centering Critical Engagement, Multimodal Learning, and Compassion through Language and Literacy - Mulcahy, Cara; Shaw, Louise (The Intersections of Critical Pedagogy, Critical Literacy, and Social Justice: Toward Empowerment, Equity, and Education for Liberation, 2024)
Keywords: dept.sed

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

Impacts of an assistive technology graduate program: a case study - Tucker, Lauren (Assistive Technology Outcomes and Benefits (ATOB), 2024)
Alumni from an Assistive Technology (AT) graduate program were invited to complete a survey and participate in focus groups to share how they are using the knowledge gained from their graduate degree and its impact on their professional careers. The sample of 27 alumni spanned seven years and a variety of professional backgrounds. This qualitative single-case study revealed impacts on careers, professional skill development, and technology skills after graduation. Participants also connected this later skill development to their concrete learning experiences within the graduate program.
Keywords: assistive technology; dept.sed; graduate program; peer-reviewed; perspectives; special education

Letter to the editor: Supporting drivers with autism and police officer interactions-Connecticut’s blue envelope program - Gleeson, M.B.; Grindle, H.; Gleeson, M.M. (Journal of Autism and Developmental Disorders, 2024)
The rising prevalence of autism spectrum disorder (ASD) has led to increased efforts to support individuals with ASD across numerous aspects of life, including driving. While obtaining a driver’s license substantially impacts quality of life and independence, it also creates distinct challenges for those with ASD. Challenges surrounding social communication, executive functioning, and sensory sensitivities are particularly evident when considering interactions between drivers with ASD and law enforcement personnel. Connecticut’s Blue Envelope Program aims to improve interactions between drivers with and ASD law enforcement by providing instructions for officers and drivers to follow during routine traffic stops on a physical, blue colored, envelope. The instructional guidelines aim to assist officers in understanding and appropriately responding to common ASD-related behaviors which may be otherwise misinterpreted and includes accommodations officers could consider during a stop. Additionally, the envelope outlines clear steps for drivers with ASD to follow through the stop as to support predictability and expectations. The widespread acceptance, efficacy and popularity of the Blue Envelope program underscores the importance of increasing awareness and understanding of ASD among law enforcement and the need for more supports to aid in these increasing interactions. Discussion is offered on a broader implementation of this program to support individuals with ASD and officers, while improving the outcomes of interactions. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: Autism; Blue envelope; Driving; Law enforcement; Police officers; dept.sed

Whither Asperger’s post DSM-5? An opinion piece - Volkmar, F.R.; Woodbury-Smith, M. (Review Journal of Autism and Developmental Disorders, 2024)
Although first described in 1944 (the year the description of infantile autism), Asperger’s syndrome attracted little attention until the publication by Lorna Wing in early 1980. Over time, different views of the definition of Asperger’s syndrome developed. By the time of the Third Edition of the American Psychiatric Association’s Diagnostic and Statistical Manual and the Tenth Edition of the World Health Organization’s International Classification of Disease, enough information had accumulated to include the condition within the broader autism category. Asperger’s syndrome remained a focus of research interest and debate until its exclusion in the DSM-5 in 2013. We argue that the decision to remove Asperger’s syndrome 10 years ago as a distinct condition was premature. A discussion of the tensions around defining Asperger’s and concerns now arising due to the lack of this diagnostic category for new cases is provided. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Asperger’s disorder; Autism spectrum disorder; Autistic disorder; Classification; DSM-5; dept.sed; peer-reviewed